Influence of Pre-professional Organizations on TEE Students (The 40th International Pupils’ Attitudes Towards Technology Conference Proceedings 2023, 2023)
Since the 1970’s, there has been a notable decrease in the number of Technology and Engineering Education (TEE) teacher preparation programs, as well as TEE teacher preparation program graduates within the United States. Previous studies have investigated reasons that post-secondary students pursue a TEE degree. However, no research is currently available regarding factors influencing student retention in TEE teacher education programs as well as factors that influence whether TEE preservice teachers enter the education field. Using the expectancy-value theory, this study investigates the relationship of participation of communities of practice in a student’s intention to graduate from the program and enter the teaching field following graduation. This is the first step to a cross-sectional study looking at the influence of exposure to and participation in the Technology and Engineering Educators Collegiate Association on TEE teacher preparation program students. Participation in TEECA was measured ordinally with varying levels of participation depending on a student’s activity level in student chapter meetings, conference attendance, and event participation.